Mitigating privacy issues on Facebook by implementing information security awareness with Islamic perspectives - Faisal, Ammy Amelia; Nisa', Bsek Salihatun; Ibrahim, Jamaludin (2013)
This paper highlights the broad range of information security awareness by providing an awareness guideline to address human vulnerabilities in social networking site. It explains the security challenges in social networking sites. These social networking sites pose great challenges on how to protect human privacy. Therefore, this paper will briefly discuss of the implementation of information security awareness in order to address privacy issues with social networking site i.e. Facebook. This paper will begin with the importance of information security to protect information assets by maintaining the confidentiality, integrity, and availability (CIA). It also focuses on the major privacy issues challenges on Facebook. The privacy issues can be mitigated with the information security awareness. This paper discusses privacy issues and security awareness from Islamic point of view to help minimize privacy issues on Facebook.